Subacute Hypophysitis with Panhypopituitarism as First Presentation of HIV and Syphilis Coinfection - Rute Alves; Margarida França (Case Reports in Infectious Diseases)
Infection by Treponema pallidum still represents a clinical challenge due to its various forms of presentation. HIV coinfection added diversity and changed the natural history of syphilis as a systemic infection. We present a rare case of subacute hypophysitis and panhypopituitarism due to an early active neurosyphilis in a previously unknown HIV coinfected patient.